2012
DOI: 10.1890/es12-00098.1
|View full text |Cite
|
Sign up to set email alerts
|

Food quality and food threshold: implications of food stoichiometry to competitive ability of herbivore plankton

Abstract: Citation: Iwabuchi, T., and J. Urabe. 2012. Food quality and food threshold: implications of food stoichiometry to competitive ability of herbivore plankton. Ecosphere 3(6):51. http://dx.doi.org/10.1890/ES12-00098.1Abstract. Exploitative competition for food resources is considered to be an important factor determining the dominant species in communities. In such a competition, a threshold food concentration (TFC), where the growth rate becomes zero, is crucial in determination of competitive outcomes. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…This is consistent with the results of Iwabuchi and Urabe (2010), who demonstrated that small cladocerans such as Ceriodaphnia quadrangula can outcompete larger Daphnia pulex even in the absence of size-selective predation due to their greater ability to benefit from P-rich bacterial food. This is also consistent with the more recent finding by Iwabuchi and Urabe (2012) that the quality of food influences the competitive superiority of a herbivore zooplankton species in terms of threshold food levels. A possible spatial adaptation of Dc is its increased efficiency in retaining the smallest food particles on fine mesh size filters in warm, and hence less viscous (Abrusan 2004) subsurface water layers during the summer stratification.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the results of Iwabuchi and Urabe (2010), who demonstrated that small cladocerans such as Ceriodaphnia quadrangula can outcompete larger Daphnia pulex even in the absence of size-selective predation due to their greater ability to benefit from P-rich bacterial food. This is also consistent with the more recent finding by Iwabuchi and Urabe (2012) that the quality of food influences the competitive superiority of a herbivore zooplankton species in terms of threshold food levels. A possible spatial adaptation of Dc is its increased efficiency in retaining the smallest food particles on fine mesh size filters in warm, and hence less viscous (Abrusan 2004) subsurface water layers during the summer stratification.…”
Section: Discussionsupporting
confidence: 93%
“…Variations C:N:P stoichiometry have been reported for microzooplankton (e.g., Meunier et al, 2012a;Grover and Chrzanowski, 2006) and for mesozooplankton (Urabe et al, 2002b;DeMott and Pape, 2005;Ferrao et al, 2007;Iwabuchi and Urabe, 2012b). Differences in elemental stoichiometry within or between the different trophic levels might help elucidate ecological interactions during food-web successions (Plath and Boersma, 2001;Sterner and Elser, 2002;Grover and Chrzanowski, 2006;Sterner et al, 2008;Meunier et al, 2012a,b;Litchman et al, 2013).…”
Section: Question 1: Does Phytoplankton Food Quality Shape the Microzmentioning
confidence: 99%
“…Variable phytoplankton elemental composition is often presumed to propagate across trophic levels in the food chain (Mitra and Flynn, 2007;Malzahn et al, 2010;Iwabuchi and Urabe, 2012b;Meunier et al, 2012a). Stoichiometric plasticity in (meso-) zooplankton seems to be both narrower and more complex than in phytoplankton (Sterner and Elser, 2002;Urabe et al, 2002a,b;Iwabuchi and Urabe, 2012a,b;Suzuki-Ohno et al, 2012;Hessen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Al tered stoichiometry of primary producers alters food quality for herbivores, which strongly influences trophic interactions and food web dynamics, constraining consumer grazing and growth rates, as well as nutrient recycling (e.g. Sterner & Elser 2002, Iwabuchi & Urabe 2012. ES has successfully been applied to explain consumer food uptake rate, assimilation and growth efficiency (Cross et al 2003, Fagan & Denno 2004, Frost et al 2006, competition between consumer species (Hall 2004, Loladze et al 2004 as well as the effects of consumers on prey nutrient composition (Daufresne & Loreau 2001, Hillebrand et al 2009b.…”
Section: Introductionmentioning
confidence: 99%